Kepedulian Novis Sang Timur Dalam Berekologi Sebagai Ungkapan Iman Di Komunitas Bandulan Malang - Genoveva Jawa; Intansakti Pius X (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
Starting from the reflections of the Sang Timur Novice Sisters in Bandulan Malang after undergoing faith deepening in the 2023 Development Fasting Action with the theme "ECO-SOCIAL JUSTICE: Caring for others and Creation as the background for this article. Ecology is the focus of attention of the Novice Sisters. The ecological crisis certainly cannot be separated from irresponsible human actions. The Novice Sisters of the East are aware that they are also part of the world. The purpose of this article is to present the results of the reflections of the Sang Timur novices in following up on the 2023 Development Fasting Action on Eco-Social Justice, namely caring for others and the natural world of creation in accordance with the spirit of the encyclical laudato si.